Revealing the depth of Nyidham Sari's metaphor: A cultural and linguistics exploration with language teaching implications - Sutaji, Ahmad Aris Mundir; Rachmadani , Budi; Suswanto, Suswanto; Muqit, Abdul (ARKA INSTITUTE, 2025)
Tembang writers typically employ words that are not literal but rather words have figurative meanings. One of those is metaphor. This study aims to analyze metaphors in Nyidham Sari songs and reveal their role in conveying cultural values and moral messages in language learning, as well as understand how traditional Javanese songs can serve as an educational tool to transmit knowledge and cultural values to contemporary learners. The data of the research are metaphors within the Nyidham Sari tembang. To analyse the data the researcher identified metaphors to understand the metaphor meaning and the function in the context of the tembang. This study employs the basic theory of the Conceptual Metaphor by Lakoff and Johnson. This study shows that Nyidham Sari tembang uses natural metaphors, journey metaphors, and cultural value metaphors to describe abstract concepts and convey deep messages. The research results indicate that metaphors in Nyidham Sari tembang play an important role in conveying cultural values and moral messages. The result of this study also has implication on language teaching, namely, teaching metaphor, interpretation skill development, teaching material, and critical thinking development. Finally, this study is expected to inspire other researchers who interest to explore metaphors in different cultural.